Somatotypes and handgrip strength analysis of elite Serbian sambo athletes - Jelena Slankamenac; Tatjana Trivić; Damjan Jakšić; Miodrag Drapšin; Nemanja Lakićević; Patrik Drid (Exercise and Quality of Life)
The aim of this study was to establish whether there are differences between weight categories in different anthropometric measurements and handgrip strength between elite Serbian male and female sambo athletes divided into weight categories. A total of 70 elite Serbian sambo athletes participated in the study, who were participants of the World Cadet Sambo Championship held in Novi Sad. Athletes are classified into categories according to gender and official weight categories. Using anthropometry, we calculated somatotypes and hand-grip strength. For statistical analysis, we used a one-way analysis of variance and Tukey’s post hoc tests to compare group differences by weight categories. Somatotype analysis shows that a typical somatotype in male sambo athletes was endomorphic mesomorphs. In female groups, the most common somatotype in the lightest categories was mesomorphic ectomorphs, and in the heaviest categories were endomorphic mesomorphs. Examining the handgrip for both left and right hand, as well as in total, shows that there is a statistically significant difference between the categories. In total, the strength of the handgrip increases progressively in groups. In male categories, the difference exists between the first 4 groups and -78kg, as well as between -42kg and -46kg and the heaviest weight category. Differences between weight categories in female athletes were found between the lightest group and last six groups in total, in favor of the last six. Anthropometric measurements revealed a statistically significant difference between weight categories. Mesomorphy was the most dominant somatotype in male categories, while female athletes differed concerning weight category. The achieved results can serve as data to compare the somatotype and handgrip strength of elite sambo athletes on a national and international level. These findings suggest that the handgrip strength and somatotypes are the keys to success in relation to the weight category.